2007
DOI: 10.1097/brs.0b013e3181557d45
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Activated Factor VII in Spinal Surgery

Abstract: No safety concerns were indicated for the use of rFVIIa in patients at all doses tested; rFVIIa reduced adjusted blood loss and adjusted transfusions during spinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In patients with trauma and coagulopathy, rFVIIa reduces fresh-frozen plasma transfusions, multiorgan failure, and acute respiratory distress syndrome [18]. Prophylactic use of rFVIIa has been tested in other surgical fields, and several randomized clinical trials have suggested that its use reduces the number of required blood cell transfusions without significantly affecting mortality [19], [20], [21].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with trauma and coagulopathy, rFVIIa reduces fresh-frozen plasma transfusions, multiorgan failure, and acute respiratory distress syndrome [18]. Prophylactic use of rFVIIa has been tested in other surgical fields, and several randomized clinical trials have suggested that its use reduces the number of required blood cell transfusions without significantly affecting mortality [19], [20], [21].…”
Section: Discussionmentioning
confidence: 99%
“…Losses of up to 4.5 liters are well-documented in the literature 1,2, as is the need for transfusion of up to eight units of red blood cell concentrate to support such procedures 3-5.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the RCTs outlined in the previous sections, off-label rFVIIa has also been studied in liver biopsy (Jeffers et al , 2002), prostatectomy (Friederich et al , 2003), pelvic fracture (Raobaikady et al , 2005), haematopoietic stem cell transplant (Pihusch et al , 2005), dengue haemorrhagic fever (Chuansumrit et al , 2005), burn patients requiring surgery (Johansson et al , 2007), spinal fusion surgery (Sachs et al , 2007), traumatic ICH (Narayan et al , 2008) and craniofacial reconstruction (Hanna et al , 2010). All these studies were small with 100 patients or less and only four had more than 50 patients (Jeffers et al , 2002; Pihusch et al , 2005; Sachs et al , 2007; Narayan et al , 2008).…”
Section: Randomised Trials Of Use Of Rfviia In Patients Without Haemomentioning
confidence: 99%
“…All these studies were small with 100 patients or less and only four had more than 50 patients (Jeffers et al , 2002; Pihusch et al , 2005; Sachs et al , 2007; Narayan et al , 2008). No mortality benefit was seen in any of these studies.…”
Section: Randomised Trials Of Use Of Rfviia In Patients Without Haemomentioning
confidence: 99%
See 1 more Smart Citation